1999
DOI: 10.1007/pl00007653
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Airway Responses in Mice

Abstract: We examined the effect of animal strain, type of spasmogen, and mode of spasmogen administration on the pattern of lung mechanical responses in intubated and mechanically ventilated mice. We determined the response in inspiratory respiratory system resistance (R(rs)) and inspiratory static respiratory system compliance (C(rs)) to increasing doses of inhaled or intravenous carbachol or serotonin in Balb/C and C57BL/6 mice. R(rs) responsiveness was quantitated by calculating, by interpolation, the inhaled spasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…However, in remodeled mucus cell metaplastic airways, pretreatment of the airway directly with the MANS peptide before stimulation with the mucus secretagogue, methacholine, attenuated airway hyperresponsiveness in response to cumulative aerosol challenge with serotonin. Serotonin has been used previously in mice models to demonstrate responsiveness of the bronchial musculature and to accentuate differences in airway responsiveness between inbred mouse strains (7,12). To our knowledge, serotonin has not been shown to influence mucin secretion, and thus the MANS peptide-related attenuation of airway hyperresponsiveness would seemingly be associated with direct effects on airway smooth muscle contraction, indirect effects on baseline airway lumens related to inhibition of mucus secretion, or indirect effects of secreted mucins on airway reactivity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in remodeled mucus cell metaplastic airways, pretreatment of the airway directly with the MANS peptide before stimulation with the mucus secretagogue, methacholine, attenuated airway hyperresponsiveness in response to cumulative aerosol challenge with serotonin. Serotonin has been used previously in mice models to demonstrate responsiveness of the bronchial musculature and to accentuate differences in airway responsiveness between inbred mouse strains (7,12). To our knowledge, serotonin has not been shown to influence mucin secretion, and thus the MANS peptide-related attenuation of airway hyperresponsiveness would seemingly be associated with direct effects on airway smooth muscle contraction, indirect effects on baseline airway lumens related to inhibition of mucus secretion, or indirect effects of secreted mucins on airway reactivity.…”
Section: Discussionmentioning
confidence: 98%
“…On appropriate stimulation, the granules translocate to the apical borders of the cell, and, following fusion of granule membranes with the cellular plasma membrane, mucins are released onto airway epithelial surfaces via an exocytotic process (4,13). Nine mucins are currently recognized to be expressed in normal respiratory tract tissues (MUC1, 2, 4, 5AC, 5B, 7,8,13,and 19;Ref. 16).…”
mentioning
confidence: 99%
“…Alternatively, ultrasonic nebulization of bronchoconstrictor solutions (mg/ml) has been successfully applied in tracheostomized, ventilated mice (22). Such a direct cholinergic challenge to the airways is advantageous over systemic challenge not only because it better simulates physiological stimulation of airway smooth muscle in humans but also because systemic delivery of agonists has been reported to affect airways via reflex or humoral mechanisms (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez et al (1999) generated a 3.1-m-diameter aerosol of serotonin or carbachol and delivered it through a cannula into the trachea of BALB/c and C57BL/6 mice. The significant differences in response, as compared to injection of these compounds, were attributed to unspecified differences between the mouse varieties.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that B6C3F 1 , C57B1/6, and DBA/2 mice demonstrate different induction levels of genotoxicity and hematotoxicity to chronic inhalation of benzene (Luke et al, 1988). More recently, Fernandez et al (1999) found differences in responses of two mouse strains (BALB/c and C57BL/6) to two common inhaled spasmogens: carbachol and serotonin. Strain-related differences in response are usually assumed to be related only to differences in metabolism or tissue sensitivity.…”
Section: Tion; Lung Castsmentioning
confidence: 98%